PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), KUALITAS PELAYANAN DAN PROMOSI TERHADAP BRAND IMAGE TELKOMSEL DI KOTA PADANG - Tifani Ratu Firdaus; idris idris (Program Studi Magister Manajemen, 2014)
This study aimed to analyze the influence of corporate social responsibility (CSR), quality of service and promotion brand image of Telkomsel in Padang. Type of research is causative. The population in this study is the people of Padang who know CSR program, feel quality of service and know the promotion by Telkomsel in Padang. Sample based on Non Probability Sampling with purposive sampling technique. Analysis of the data used multiple regression and hypothesis testing using F-test and t-test. The results of this study indicate that 1) corporate social responsibility (CSR) have a significant influence on brand image of the Telkomsel in Padang. 2) The quality of service have a significant influence on brand image of Telkomsel in Padang. 3) Promotion have a significant influence on brand image of Telkomsel in Padang. From the research, it appears that the promotion variables have a greater influence than the variables CSR and quality of service. Furthermore, CSR variables has the second largest effect than the variable quality of service and variables that have the smallest effect in this study is the variable quality of service. So that means the promotion variables have a very important role in enhancing the brand image of the Telkomsel in Padang. Keywords : corporate social responsibility (CSR), quality of service , promotion, brand image.